2022
DOI: 10.3390/ijms23158717
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable-Glass-Fiber Reinforced Hydrogel Composite with Enhanced Mechanical Performance and Cell Proliferation for Potential Cartilage Repair

Abstract: Polyvinyl alcohol (PVA) hydrogels are promising implants due to the similarity of their low-friction behavior to that of cartilage tissue, and also due to their non-cytotoxicity. However, their poor mechanical resistance and insufficient durability restricts their application in this area. With the development of biodegradable glass fibers (BGF), which show desirable mechanical performance and bioactivity for orthopedic engineering, we designed a novel PVA hydrogel composite reinforced with biodegradable glass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…It has been reported that the addition of fibers reinforces the composite, increasing its mechanical strength [ 40 ]. For example, Zhu et al fabricated a glass fiber-reinforced polyvinyl alcohol hydrogel composite, which exhibited desirable mechanical performance in cartilage repair [ 41 ]. Cai et al designed a novel calcium phosphate bone cement with enhanced mechanical performance by adding poly(lactide-co-glycolic acid) nanofibers to the solid phase [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the addition of fibers reinforces the composite, increasing its mechanical strength [ 40 ]. For example, Zhu et al fabricated a glass fiber-reinforced polyvinyl alcohol hydrogel composite, which exhibited desirable mechanical performance in cartilage repair [ 41 ]. Cai et al designed a novel calcium phosphate bone cement with enhanced mechanical performance by adding poly(lactide-co-glycolic acid) nanofibers to the solid phase [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…An aqueous PVA solution was subjected to repeated freeze-thaw cycles to crystallize the molecular chains and form hydrogels [ 72 ]. PVA hydrogels are used as biomaterials in artificial cartilage and joints [ 73 ].…”
Section: Hydrogel and Artificial Cell Sheetsmentioning
confidence: 99%
“…Even if the amount of fiber added was low and had no evident impact on the soil, it is important to consider its presence in the end-of-life scenario of these materials. However, in the same way as biodegradable glass fibers have been developed in recent literature, 35 it is not unlikely that biodegradable carbon fibers will be available in the future. Here, studies addressing a sustainable engineering process report the commercial production of biobased carbon fibers based on cellulose and lignin, 36 which is the first step to designing future biodegradable CF.…”
Section: Carbon Fiber and Extruded Biocompositementioning
confidence: 99%